Do people with psychosis engage in unhelpful metacognitive coping strategies? A test of the validity of the Cognitive Attentional Syndrome (CAS) in a clinical sample. (January 2018) - Sellers, Rachel; Wells, Adrian; Parker, Sophie; Morrison, Anthony P.
Abstract: The Self-Regulatory Executive Function (S-REF) model assumes that unhelpful metacognitive coping strategies characterised by worry, rumination, threat monitoring and attempts to control thoughts, have a central role in psychological disorders and prolonged negative affect. Collectively, these strategies constitute the Cognitive Attentional Syndrome (CAS). This research aims to test whether a questionnaire designed to capture these responses (the CAS-1: Wells, 2009, p. 268) is a valid assessment tool in clinical psychosis, and to test whether activation of the CAS is associated with positive and negative outcomes. A sample of 60 people with psychosis completed a semi-structured interview about psychotic symptoms, the CAS-1 self-report measure and validated self-report measures of metacognitive beliefs, negative affect, quality of life and recovery. The CAS-1 demonstrated good internal consistency, concurrent validity and predictive validity. Hierarchical multiple regression analyses revealed that negative metacognitive beliefs predict negative affect, perceptions of recovery and quality of life in people with psychosis over and above psychotic symptoms. CAS-1 scores did not contribute additional variance in the final regression models. Implications for theory and clinical practice are discussed. Highlights: The CAS-1 is a valid measure of metacognitive coping strategies in psychosis. Metacognitive beliefs are a better predictor of outcome than CAS-1 processes. Negative metacognitive beliefs predict distress, quality of life and recovery.